Rencana dan Target Birama sebagai Pemicu Optimalisasi Capaian Praktik Individual Vokal Klasik di Jurusan Musik, Fakultas Seni Pertunjukan, Institut Seni Indonesia Yogyakarta - A. Gathut Bintarto T. (Jurnal Kajian Seni, 2017)
The effective efforts on higher education of arts including many improvement aspects such as cognitive and skill. The Western vocal study on Music Department, Performance Art Faculty of ISI Yogyakarta has several challenges such as limited duration of study, the complexity of historical background of the repertoar and the needs to study at leastfour different songs from foreign languages. The way to manage the sensation of the unseen vocal cord combined with the needs of the student to make adaptations to the higher educational systems lead to the thought of using the student’s planning form and individual progress report on their vocal study. This aids helped to observe the individual skill progress, the changing of the student’s attitude and emotions, make it easier forthe teacher to maintain the study and also anticipating the habit of postponing the final exam. Through action research method, the usage of the student’s planning form and individual progress report serves as trigger and guidance to make further comprehension on individually characteristic of each voice and the forming of the singer’s attitude through controlling his/her emotions.